Classical results via Mann-Ishikawa iteration - Ştefan M. Şoltuz; Diana Otrocol (Journal of Numerical Analysis and Approximation Theory, 2007)
New proofs of existence and uniqueness results for the solution of the Cauchy problem with delay are obtained by use of Mann-Ishikawa iteration.